청소년 읽기 부진 학생들의 읽기 특성 분석 및 읽기 부진의 유형 분류 - 최숙기; Choi Sookki (독서연구, 2017)
본 연구는 국내 청소년 읽기 부진 학생들의 읽기 특성을 탐색하고, 읽기부진의 특성에 따른 유형을 분류하는 데 그 목적이 있다. 읽기 부진 학습자에 대한 일반적 정의는 해당 학년 수준에 기대되는 읽기 능력에 미치지 못하는 독자를 의미하며 난독증과 같은 읽기 장애의 범주와 낮은 읽기 성취나 읽기 지체와 같은 읽기 저성취 범주를 동시에 포괄한 개념이다. 청소년 시기에 발생하는 읽기 문제는 학업 결손에 의한 성취 격차, 후속적인 삶의 적응 문제를 유발하므로 반드시 해결하여야 할 주요 교육적 문제에 해당하다. 또한 PISA 국제 읽기 성취도 평가와 국어 성취도 평가에서 읽기 기초학력 부진 학습자의 비율 확대는 청소년 읽기 부진에 대한 주의를 더욱 요구하고 있다. 이에 본 연구에서는 김윤옥 외(2014)의 난독증 선별 체크리스트(Dyslexia Screening Scale: DySC)와 추가된 독해 어려움 진단 문항을 활용하여 학업성취도 평가에서 기초학력 이하 집단에 해당하거나 학교에서 실시하는 국어 교과 시험에서 하위 10% 수준에 해당하는 학생 중 읽기 부진 집단으로 추정된 중·고등학생 384명을 대상으로 하여 분석을 실시하였다. 이를 통해 청소년 읽기 부진의 수준과 특성을 탐색하고, 청소년 읽기 부진 집단의 유형을 분류함으로써 향후 중학교와 고등학교 청소년 독자를 대상으로 한 읽기 부진 진단 검사를 위한 변인 설정 및 지도 방향에 대한 유의한 정보를 제공하고자 하였다. This study explores the level and aspects of reading difficulties of struggling readers in Korean secondary school and then struggling readers profile using cluster analysis. 384 secondary students(180 middle school students, 204 high school students) were screened for reading difficulties, using Dyslexia Screening Scale(DySC) developed by Kim et al.(2014). They were readers at or below reading basic proficiency level of korean language achievement test and achieved below bottom 10% of Korean language subject test. Their all mean score of DySC was 1.44(middle school students=1.50, high school students=1.38). And their mean score of 3 critical reading proficiency constructs(decoding, reading fluency, comprehension) was 1.54(middle school students=1.57, high school students=1.51). These scores were higher than elementary school students with dyslexia. They showed over average reading difficulty score in comprehension, additional reading effects, executive function, talent and showed below average reading difficulty score in oral skill, family history, left/right brain dominance. Cluster analysis demonstrated that the korean adolescents were classified two struggling reader clusters and they had statistically significant difference in 8 reading comprehension difficulties.